The Head Of School Strategy in The Development of Teacher Professional Competence - Purnomo, Awan; Ahmad, Syarwani; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The main problem facing education today is the quality of human resources are low and not willing follow the progress of science and technology in the era of globalization, where competition quality to be something very urgent met by the school, then you need to do is improve the quality of human resources, both from the aspect of intellectual, spiritual, creativity, morality, and responsibility. This study aims to determines how the principal strategy in improving the competence of teachers in terms of pedagogical, professional, personal and social. Effort headmaster to the make-up of professional interest of teacher can support the attainment of education target at school. This research uses the descriptive method with the approach qualitative. The technique of data collecting used is observation, interview, and documentation. Subjek Research is: Headmaster, Proxy of Headmaster and Pre-Eminent teacher SMA Negeri 4 OKU